Exploring the Correlation of Religious Moderation, Character Education, and Ethics with Students’ Aqidah Learning Performance - Muhammad Romdloni Putra; Siti Maisyaroh (Ar-Fachruddin: Pendidikan Agama Islam, 2025)
Research Objective– This study aims to explore the structural relationships between religious moderation, character education, ethics, and students’ Aqidah learning performance at the Madrasah Aliyah level, and to examine how these value-based constructs collectively contribute to measurable academic outcomes. Methodology– A quantitative correlational design was employed involving 75 students of MA Al-Hidayah Betoyo Kauman, Gresik. Data were collected through validated Likert-scale questionnaires and triangulated with teacher performance records. Statistical analyses included descriptive statistics, Pearson correlation, multiple regression, and Structural Equation Modeling (SEM) using SPSS and AMOS. Findings– The results indicate significant positive correlations among all variables. Character education emerged as the strongest predictor of Aqidah performance (β = .37), followed by ethics (β = .33) and religious moderation (β = .29). SEM analysis confirmed both direct and indirect effects, with religious moderation influencing performance through character education and ethics. The model demonstrated satisfactory fit indices and explained 54% of the variance in learning performance. Research Implications/Limitations– The study highlights the importance of integrating moderation, moral reasoning, and character formation in Aqidah instruction. However, the limited sample size and single-school context restrict generalizability. Originality/Value– This research advances Islamic education discourse by empirically modeling the interconnected influence of moderation, character, and ethics within a unified SEM framework